Determining the different learning styles of students from different engineering programmes in UNITEN - Long C.Y.; Jern K.P.; Khalid N.H.B.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Students nowadays learn differently from their forefathers. Therefore, there is a need for the educators to identify the way the students learn. This research aims to study the major learning styles of students from different engineering programmes and their differences in University Tenaga Malaysia. This paper will also report on the analyses of types of learning styles of the students. © 2013 IEEE.